Elevated hyaluronan and extracellular matrix metalloproteinase inducer levels in women with preeclampsia - Romão, Mariana [UNESP]; Weel, Ingrid Cristina [UNESP]; Lifshitz, Shirlee Jaffe; Peraçoli, Maria Terezinha Serrão [UNESP]; Witkin, Steven Sol [UNESP] (Springer Nature, 2013)
Purpose: Preeclampsia (PE) is a specific syndrome of pregnancy clinically identified by hypertension and proteinuria from the 20th week of gestation associated with a systemic inflammatory response and oxidative stress. While pro-inflammatory cytokines have been extensively studied in PE, other factors in the circulation that also influence the magnitude of inflammation have received much less attention. The present study compared serum concentrations of five immune-regulatory compounds in normotensive pregnant women and in women with gestational hypertension (GH) or PE. Methods: Sixty women with PE, 53 with GH and 40 normotensive women paired by gestational age were evaluated. Sera were evaluated for concentrations of extracellular matrix metalloproteinase inducer (EMMPRIN), hyaluronan, gelsolin, visfatin and histone 2B by ELISA. Differences between groups were analyzed by nonparametric tests, with a significance level of 5 %. Results: Increased levels of EMMPRIN and hyaluronan were present in preeclamptic women as compared to the GH and normotensive groups. There was no difference between groups in gelsolin, visfatin or histone 2B. Conclusion: Increased release of EMMPRIN and hyaluronan may contribute to an elevated pro-inflammatory response and tissue damage in women with PE. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: EMMPRIN; Gestational hypertension; Hyaluronan; Inflammation; Preeclampsia